2012
DOI: 10.1080/02786826.2011.617399
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube and Fullerene Emissions from Spark-Ignited Engines

Abstract: Particles were collected from the exhaust of Indian autorickshaws with natural gas and gasoline-fueled spark-ignited engines. Transmission electron microscopy was used to determine the size and shape of 2121 systematically selected particles. Particles were largely soot agglomerates and other types documented in the literature, but approximately 10% of the nonvolatile particles were multiwalled carbon nanotubes and fullerenes, forms of crystalline carbon distinct from soot. Autorickshaw fullerenic particle num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…It should be noted that the suspended SWCNTs tend to form agglomerates due to their geometry and van der Waals forces, as supported by the aerodynamic size distribution (Supporting Information Figure S1) and previous measurements of CNTs collected directly from engine exhaust 17 and other flame exhausts. 18 While a kinetic limitation to the oxidation of internal SWCNTs in the agglomerates of the current experiments may occur, it is also likely to occur in the atmosphere.…”
Section: ■ Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It should be noted that the suspended SWCNTs tend to form agglomerates due to their geometry and van der Waals forces, as supported by the aerodynamic size distribution (Supporting Information Figure S1) and previous measurements of CNTs collected directly from engine exhaust 17 and other flame exhausts. 18 While a kinetic limitation to the oxidation of internal SWCNTs in the agglomerates of the current experiments may occur, it is also likely to occur in the atmosphere.…”
Section: ■ Introductionmentioning
confidence: 97%
“…9 However, it is recognized that inhalation of manufactured nanoparticles (MNPs) including CNTs in ambient air will be an important pathway for population exposure in the future, 16 as the MNPs are possibly emitted through the degradation of their end products or during their manufacture. They have also recently been found in diesel exhaust (MWCNTs) 17 and other flame exhausts. 18 Once emitted into the atmosphere, chemical modification of CNTs may occur through the oxidation by O 3 , OH, and NO 3 radicals and by the reaction with, or condensation of, pre-existing ambient organic species.…”
Section: ■ Introductionmentioning
confidence: 99%
“…• C) low-velocity jet impinging on a TEM grid (slightly above ambient temperature) as described by Lagally et al (2012). For this flow configuration, the aerodynamic cut-off diameter (d 50 ) is approximately 300 nm; nearly all particles sampled are below this size but it is likely that impaction contributed to the large particle sizes observed by microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, it was reported about the identification of fullerenes in an atmospheric carbon-containing aerosol [20,21]. Fullerene soot can get into the atmosphere as a result of combustion processes of natural gas [22], fuel (including aviation fuel) [23][24][25][26], coal [20] and biomass [27]. Earlier, it was reported that polycyclic aromatic hydrocarbons in the combustion process can turn into soot containing fullerenes [28].…”
Section: Resultsmentioning
confidence: 99%